L'éducation: quelques jalons, 1910-1964 - Allard, Michel; Baillargeon, Normand (Le Devoir: reflet du Québec au 20e siècle, 1994)

Tendances radicales du protestantisme à Montréal - Baum, Gregory (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Protestants

Grandeur et misère d'un antiduplessisme de 1947 à 1959 - Clavette, Suzanne; Comeau, Robert (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Devoir (Le)

La pensée politique de L'Action française de Montréal, 1917-1928 - Dupuis, Jean-Claude (Les Cahiers d'histoire du Québec au XXe siècle, 1994)
issued: 1994-22-00
Keywords: Action française (L'); Idéologies

Les directeurs du Devoir et l'opinion: élections, langue et Constitution - Ferretti, Lucia (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Devoir (Le); Langue; Élections

Manifeste, octobre 1970 - Horguelin, Christophe; Front de Libération du Québec (Quartier libre, 1994)
Keywords: Crise d'octobre; Front de Libération du Québec

"Ce siècle avait dix ans..." 1910-1939 - Lahaise, Robert (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Devoir (Le)

De la Guerre à la... Révolution tranquille, 1939-1964 - Laliberté, Jean-Marc (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Devoir (Le)

Une opposition farouche au suffrage féminin, 1913-1940 - Lamoureux, Diane (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Devoir (Le); Femmes; Élections

Le nationalisme de Roger Duhamel, 1927-1947 - Langevin, Martin (Les Cahiers d'histoire du Québec au XXe siècle, 1994)
issued: 1994-24-00
Keywords: Montréal-Matin; Nationalisme

Les Québécoises et leur citoyenneté. La citoyenneté selon Éva Circé-Côté - Lévesque, Andrée (La Politique des droits. Citoyenneté et construction des genres au 19e et 20e siècles, 1994)
Keywords: Circé-Côté; Éva; Femmes; Féminisme; Journalistes; Élections

Trajectoires du féminisme contemporain, 1970-1990 - Maillé, Chantal (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Femmes; Féminisme

La formation des intellectuels québécois dans l'entre-deux-guerres - Pomeyrols, Catherine (Université Michel de Montaigne-Bordeaux 3, 1994)
Keywords: Laurendeau; André; Minville; Esdras

Retailing Fashion in Montreal: A Study of Stores , Merchants and Assortments, 1845-1915 - Sifton, Elizabeth (Université Concordia, 1994)
Keywords: Commerce de détail; Marchands; Vêtements

Afro-Canadian Activism in the 1960s - Stamadianos, Peter (Université Concordia, 1994)
Afro-Canadian activism became increasingly militant in the 1960s. The rise in militancy in the Afro-American leadership of the 1960s was one factor contributing to the new era of black politics in Canada. Increased immigration from the West Indies also encouraged the proliferation of Afro-Canadian organizations dedicated to challenging racial discrimination. Afro-Canadian activism, however, developed in a substantially different manner than black politics in the United States. On the whole, most Afro-Canadian organizations and leaders were considerably less militant in their tactics and strategies than their counterparts in the United States. Internecine divisions over ancestral origin were also more pronounced in Canada where the black population was ethnically heterogeneous when compared to the Afro-American community.
Keywords: Africains; Noirs

Exchange of Opinion in the Canadian Press on the Eve of the Union, 1839-1840 - Williams, Garth (Université de Montréal, 1994)